2021
DOI: 10.1016/j.scitotenv.2021.146133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and stability of SARS-CoV-2 RNA on Bangladeshi banknotes

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
13
0
2
Order By: Relevance
“…In Italy, surfaces were samples 2-3 months after the national epidemic peak [27]. No information was found in the other studies [30,[57][58][59].…”
Section: Public Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Italy, surfaces were samples 2-3 months after the national epidemic peak [27]. No information was found in the other studies [30,[57][58][59].…”
Section: Public Surfacesmentioning
confidence: 99%
“…There were no attempts to detect infectious virus (Table 3). In seven of eight studies, it was not described if any of the sampled surfaces was cleaned or disinfected before the sampling took place [11,27,30,[55][56][57]59]. In one study, however, samples were taken four hours after surface disinfection with 1000 ppm sodium hypochlorite [58].…”
Section: Public Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus was much more stable at 4˚C. However, the stability of SARS-CoV-2 on credit card or coin has not been reported, and there has been a lack of environmental testing outside of the laboratory, with the exception of a study in Bangledesh reporting detection of SARS-CoV-2 RNA on approximately 7% of circulating banknotes [38,39]. In order to better understand the risk of paper money versus credit cards as fomites for SARS-CoV-2 in the U.S.A., the stability of the virus on U.S.A $1 banknotes, coin and money cards in the laboratory is studied herein.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fear and speculations, to the best of our knowledge, there is scarcity of studies looking for the carriage of SARS-CoV-2 on the surface of currency in circulation in community. Only a recent study from Bangladesh reported presence of SARS-CoV-2 in approximately 7% of currency samples collected from the community (Akter et al, 2021). Therefore, the present study was performed to screen the Bahraini currency in circulation in the community for any potential carriage of SARS-CoV-2 by screening by Rapid Antigen Detection Test (RADT) and Real-time PCR (RT-PCR).…”
Section: Introductionmentioning
confidence: 99%